Polymers, metal compounds and new materials - Gutsanu, Vasile (Cambridge Scholars Publishing, 2020)
This book discusses the interaction of strongly basic anion exchangers with some metal cations. These polymers are a high tonnage production of the chemical industry, and are widely used in various chemical and technical operations, particularly in the treatment of water at thermal and atomic power stations. Their interaction with metal cations, especially with iron, an unpredictable and uncontrollable process, leads to their intoxication and rapid exhaustion. However, if the interaction of these polymers with cations is controlled, then in the polymer phase, ultra-fine particles of the compounds are formed, that radically change their physical and chemical properties.